SOCS3 revisited: a broad regulator of disease, ready for therapeutic use? - STEVENSON, NIGEL (Springer, 2016)
Since their discovery, SOCS have been characterised as regulatory cornerstones of intracellular signalling. While classically controlling the JAK/STAT pathway, their inhibitory effects are documented across several cascades, underpinning their essential role in homeostatic maintenance and disease. After 20 years of extensive research, SOCS3 has emerged as arguably the most important family member, through its regulation of both cytokine- and pathogen-induced cascades. In fact, low expression of SOCS3 is associated with autoimmunity and oncogenesis, while high expression is linked to diabetes and pathogenic immune evasion. The induction of SOCS3 by both viruses and bacteria and its impact upon inflammatory disorders, underscores this protein’s increasing clinical potential. Therefore, with the aim of highlighting SOCS3 as a therapeutic target for future development, this review revisits its multi-faceted immune regulatory functions and summarises its role in a broad ranges of diseases.
PUBLISHED
Keywords: Rheumatoid arthritis; Cancer; Diabetes; Infection; Suppressor of cytokine signalling (SOCS); Janus kinase/signal transduction and activator of transcription (JAK/STAT); Immunology, Inflammation & Infection